Application Of Artificial Intelligence In Learning And Teaching Activities In The Village - Djunaedi, Djunaedi; Hanasi, Raihan A.; Susilawati, Susilawati; Fikri, Maiza; Simatupang, Septian; Fauzan, Fauzan; Syahrul, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Artificial Intelligence (AI) has become an increasingly important field in the current era of digital transformation. Artificial Intelligence (AI), is a technology designed to make computer systems able to imitate human intellectual abilities. Artificial intelligence (AI) allows computers to learn from experience, identify patterns, make decisions, and complete complex tasks quickly and efficiently. Artificial Intelligence (AI) is able to connect every device, so that someone can automate all devices without having to be on site. More than that, currently there are many machines that can interpret certain conditions or events with the help of Artificial Intelligence (AI). The processes that occur in Artificial Intelligence (AI) include learning, reasoning, and self-correction. The implementation of AI in human workmanship is to obtain optimal performance results with fast processing times and maximum results. In today's modern era, artificial intelligence (AI) is very necessary to make activities easier, especially in rural areas. So that the village becomes a modern village and is more advanced with today's technology. Therefore, this Community Service was carried out in Cisadane Village, Kwandang District, North Gorontalo Regency, Gorontalo Province. In obtaining the data used were observation and literature study. This service activity is an effort to apply artificial intelligence (AI) in learning and teaching activities in Cisadane Village, Kwandang District, North Gorontalo Regency, Gorontalo Province. This effort was motivated by the lack of implementation and lack of human resources in artificial intelligence (AI) technology in Cisadane Gorontalo Village, which resulted in artificial intelligence (AI) technology in Cisadane Gorontalo Village not being optimal. As a form of the author's thinking, several efforts and breakthroughs are offered, namely; 1.) The role of Artificial Intelligence (AI) for the people of Cisadane Village in creating a modern and technology-literate Village, by making all activities in the village easier. 2.) Increasing Human Resources in utilizing Artificial Intelligence (AI) Technology, which previously did not know, became aware so that can advance the village. Keywords : Artificial Intelligence, AI, Cisadane Village, Community Service